The Influence of Attitude and Motivation of STIKES Bina Usada Bali’s Nursing Students to Their Entrepreneurial Intention - I Gede Wirajaya; Nina Rismawati Hakim; Alfiery Leda Kio (Universitas STRADA Indonesia, 2021)
The effort of solving the problem of unemployment and decreasing its number, give in a chance for entrepreneurship to be the alternative choice of action. This current research is aimed to see the result of The Influence of Attitude and Motivation of STIKES Bina Usada Bali’s Nursing Students to Their Entrepreneurial Intention. The cross sectional design was implemented in this research. The data were collected in September 2020 through questionnaire distributed to 100 students of nursing. The data analysis using Kendall’s Tau. The bivariate analysis of Kendall’s Tau correlation value showed the significant and strong influence between the attitude and the nursing students’ entrepreneurial intention. The higher the attitude of entrepreneurship relevantly indicates the higher entrepreneurial intention (the value of r=0.780; p<0.0001). The same result occurred in the variable of motivation and the entrepreneurial intention as there was a significant and strong influence with the value of r=0.768 and p<0.0001.